Attitude and influencing factors of patients with schizophrenia toward long-acting injections: A community-based cross-sectional investigation in China - Sun, Yiying; Tong, Jie; Feng, Ying; Fang, Haiping; Jiang, Tao; Zhao, Liping; Wang, Qiang; Yang, Yi (Frontiers in Public Health, 2022)
Background: Low prescription rates of antipsychotic long-acting injections (LAIs) may be a major challenge in the prevention and treatment of schizophrenia. However, there are few studies on the usage and attitude towards LAIs among community-based patients with schiz-ophrenia. Methods: A large community-based cross-sectional investigation was conducted among 6336 patients with schizophrenia from Shanghai, China from March 1 to June 30, 2021. The structured Attitude and Status towards Treatment of Community Patients with Schizophrenia Questionnaire (AST-CSQ) was used to investigate the attitude and influencing factors of community-dwelling patients with schizophrenia towards LAIs. Results: Among the 6336 participants, the average age was 49.28±11.23. The rate of agree-ment to LAI antipsychotics among participants was 3.16% (n=200). The number of hospital-izations in the LAIs group was higher than that in the non-LAIs group, and the course of dis-ease was less than that in the non-LAIs group. There was a significant difference between them (p<0.001). The source of medical expenses, care ability, and number of hospitalizations were positively correlated with attitude towards LAIs (r=0.008 to 0.053, p<0.05). Age, fami-ly financial resources, guardian relationship, social activities, course of disease, hospitalization, outpatient compliance, history of antipsychotic use, and attitude towards oral antipsychotics were significantly negatively correlated with attitude towards LAIs (r=-0.090 to -0.028, p<0.05). Furthermore, age (OR 0.964, 95% CI 0.947-0.982), marital status (OR 1.267, 95% CI 1.002-1.602), care ability (OR 2.032, 95% CI 1.437-2.875), outpatient compliance (OR 0.510, 95% CI 0.358-0.725), antipsychotic compliance (OR 2.509, 95% CI 1.092-5.764), and attitude towards oral antipsychotics (OR 0.258, 95% CI 0.103-0.646) were significant predictors of attitude towards LAI antipsychotics. Conclusions: The community-dwelling patients with schizophrenia in China had a low will-ingness to use LAIs. The patients' age, care ability, outpatient compliance, antipsychotic compliance, and attitude towards oral antipsychotics were significantly correlated with their willingness to take LAIs. Under the global deinstitutionalized management model of mental disorders, these results highlight an urgent problems for public mental health service providers and policy-makers and provide more solutions for them.